CHARACTERISTICS AND TYPOLOGY OF DAIRY CATTLE FARMING SYSTEMS IN WEST REGION OF ALGERIA - Zakaria MESKINI; Nadra RECHIDI-SIDHOUM; A. El-Amine DAHOU; Khalil BOUNAAMA; Abdelkader HOMRANI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this study was to show the characteristics and to carry out a typology to define the different types of dairy cattle breeding in the state of Relizane, through an analysis of multiple correspondences, followed by an ascending hierarchical classification. The study was carried out in 73 dairy farms with 2,454 cattle including 1,432 dairy cows. The results show that 16% of farmers have not owned agricultural land, and that the utilized agricultural area of the surveyed farms is small on average to 7.47 ha, with an average fodder agricultural area of 3.9 ha which influences negatively on the feed self-sufficiency of farms and plays a preponderant role in poor feed management. The use of corn silage is practiced on 18% of farms. Breeders have an average cattle herd of 33.6 heads, 58.3% of which is represented by dairy cows. The racial composition of the cows is dominated by the imported breeds mainly the Holstein and the Montbéliarde with 57% and 34% respectively. The average number of human work units is 2.21 HWU/farm and in 47% of the farms the staff is exclusively family. The typology revealed six types of farms; these farms are mainly differentiated by the full agricultural area, the utilized agricultural area, the Forage area, the irrigated agricultural area, and by the cattle and dairy cow’s population.